All Solid State Chromium(III) Selective Potentiometric Sensor Based on 2‐(1‐(2‐((3‐(2‐Hydroxyphenyl)‐1H‐pyrozol‐1‐yl)methyl)benzyl)‐1H‐pyrazol‐3‐yl)phenol. Issue 10 (10th September 2014) - Kumar, Pankaj; Kumar, Sanjeev; Jain, Sapna; Lamba, Bhawna Y.; Joshi, Girdhar; Arora, Shefali
Abstract Highly selective all solid state electrochemical sensor based on a synthesized compound i.e. 2‐(1‐(2‐((3‐(2‐hydroxyphenyl)‐1H‐pyrozol‐1‐yl)methyl)benzyl)‐1H‐pyrazol‐3‐yl)phenol (I) as an ionophore has been prepared and investigated for the selective quantification of chromium(III) ions. The effect of various plasticizers, viz. dibutyl phosphonate (DBP), dibutyl(butyl) phosphonate (DBBP), nitrophenyl octyl ether (NPOE), tris‐(2‐ethylhexyl)phosphonate (TEP), tri‐butyl phosphonate (TBP), dioctyl phthalate (DOP), dioctyl sebacate (DOS), benzyl acetate (BA) and acetophenone (AP) along with anion excluders NaTPB (sodium tetraphenyl borate) and KClTPB (potassium(tetrakis‐4‐chlorophenyl)borate was also studied. The optimum composition of the best performing membrane contained (I):KClTPB:NPOE:PVC in the ratio 15 : 3 : 40 : 42 w/w. The sensor exhibited near Nernstian slope of 20.1±0.2 mV/decade of activity in the working concentration range of 1.2×10−7–1.0×10−1 M, and in a pH range of 3.8–4.5. The sensor exhibited a fast response time of 10 s and could be used for about 5 months without any considerable divergence in potentials. The proposed sensor showed very good selectivity over most of the common cations including Na+, Li+, K+, Cu2+, Sr2+, Ni2+, Co2+, Ba2+, Hg2+, Pb2+, Zn2+, Cs+, Mg2+, Cd2+, Al3+, Fe3+and La3+. The activity of Cr(III) ions was successfully determined in the industrial waste samples by using this sensor.